Implementation of three colour marker in traffic conditioner for DIFFSERV Network Simulator / Lim Lee Wan - Lim , Lee Wan (2004)
The Differentiated Services (DiffServ) is a architecture has been proposed to achieve scalability by aggregating traffic classification state, which is conveyed by means of IP-layer packet marking using the DS field. In order to ensures that the QoS requirements for each customer are met, the incoming traffic will be separate into different classes to provide a better level of service to all those packed that lie within the traffic profiles, which contracted and internet service providers. The network simulator is a tool to analyze and study the behavior of DiffServ networks without the existing of the real network. The Simulation of the simulator will show the results that initiate the real network environment. The main purpose of this project is to implement the three colour market for traffic conditioning in the DiffServ network simulator. In this project, there are two types of three colour market which user is allowed to choose either one for the network simulator. There colour marker is to govern how traffic is marked and conditioned upon entry to a DiffServ network. Finally, object oriented approach will be used for the development of the three colour market in traffic conditioner by using Java programming language.